Mobilization of Transplanted Bone Marrow Mesenchymal Stem Cells by Erythropoietin Facilitates the Reconstruction of Segmental Bone Defect - Jun Li; Zeyu Huang; Bohua Li; Zhengdong Zhang; Lei Liu (Hindawi Limited, 2019)
Reconstruction of segmental bone defects poses a tremendous challenge for both orthopedic clinicians and scientists, since bone rehabilitation is requisite substantially and may be beyond the capacity of self-healing. Bone marrow mesenchymal stem cells (BMSCs) have been identified as an optimal progenitor cell source to facilitate bone repair since they have a higher ability for proliferation and are more easily accessible than mature osteoblastic cells. In spite of the potential of BMSCs in regeneration medicine, particularly for bone reconstruction, noteworthy limitations still remain in previous application of BMSCs, including the amount of cells that could be recruited, the compromised bone migration of grafted cells, reduced proliferation and osteoblastic differentiation ability, and likely tumorigenesis. Our current work demonstrates that BMSCs transplanted through the caudal vein can be mobilized by erythropoietin (EPO) to the bone defect area and participate in regeneration of new bone. Based on the histological analysis and micro-CT findings of this study, EPO can dramatically promote the effects on the osteogenesis and angiogenesis efficiency of BMSCs in vivo. Animals that underwent EPO+BMSC administration demonstrated a remarkable increase in new bone formation, tissue structure organization, new vessel density, callus formation, and bone mineral density (BMD) compared with the BMSCs alone and control groups. At the biomechanical level, we demonstrated that combing transplantation of EPO and BMSCs enhances bone defect reconstruction by increasing the strength of the diaphysis, making it less fragile. Therefore, combination therapy using EPO infusion and BMSC transplantation may be a new therapeutic strategy for the reconstruction of segmental bone defect.